Balanced scorecard como ferramenta de gestão aplicada a unidade hospitalar privada - Santos, Adriano Macedo dos (2011)
In this study the objective is to implant Balanced Scorecard administration for the development of a Strategic Map, for the support of the electric outlet of decisions in the administration of operations of an unit of attendance doctor-hospitalar. The present work presents a case study developed at a private hospital in the State of Rio Grande do Norte. The collection of data was developed after the analysis of the revision of the literature, and he/she had as critical judgement of evaluation used by the following Unit. The work is concluded in the proposition of a strategic map that elevates the return on investment (financial perspective), in the item profitability and growth. In the search of the customer's satisfaction (customer's perspective), that is nothing else than it already exists inside of the Unit in study, just needing to be organized and aligned with the executive picture and the other collaborators. The requirements competitiveness, information, innovation and technology (perspective of the internal processes), they were indispensable to eliminate the re-work, waste and to improve the automation. It is finally, the investment and development of innovation mechanisms, they enlarge important competitive advantage in the processes for creation of value, through the ability, attitude and knowledge (perspective of the learning and growth). As one of the results of this study a strategic map was developed, looked for in Balanced Scorecard, for support in the electric outlet of decisions of the administration of operations of an Unit Doctor- Healthcare